Keeping families engaged: the effects of home-based family therapy enhanced with experiential activities - Thompson, Sanna J. (2009)
Engagement of high-risk adolescents and their families in treatment is a considerable challenge for service providers and agencies. Despite its importance, little research has been conducted that explores this important treatment process. To address this gap, a test of an innovative method to improve engagement in family therapy was undertaken. Findings of this study of 42 intervention group families and 41 comparison group families (N=83) suggest that augmenting in-home family therapy with short and creative experiential activities can significantly increase engagement and retention in treatment. Further research of engagement as a mechanism of change in family-based treatment is needed.